2004
DOI: 10.1021/jp047250c
|View full text |Cite
|
Sign up to set email alerts
|

Excitation-Wavelength-Dependent Fluorescence Behavior of Some Dipolar Molecules in Room-Temperature Ionic Liquids

Abstract: The fluorescence behavior of several dipolar molecules has been studied in three room-temperature ionic liquids, namely, [BMIM][BF4], [EMIM][BF4], and [BMIM][PF6], as a function of the excitation wavelength. Although a large majority of these systems show normal fluorescence behavior with no excitation wavelength dependence, a few systems surprisingly exhibit fairly strong excitation-wavelength-dependent fluorescence behavior in these media. The excitation-wavelength-dependent shift of the fluorescence maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
252
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(267 citation statements)
references
References 56 publications
14
252
1
Order By: Relevance
“…‡ § The most compelling experimental evidence supporting this prediction is given by a striking finding by Samanta and coworkers (23,24). In their study of time-dependent fluorescence of dipolar molecules in imidazolium-based liquids, they observed that ANF exhibits an excitation-wavelength-dependent fluorescence spectrum.…”
Section: Gs(r T*)mentioning
confidence: 96%
See 2 more Smart Citations
“…‡ § The most compelling experimental evidence supporting this prediction is given by a striking finding by Samanta and coworkers (23,24). In their study of time-dependent fluorescence of dipolar molecules in imidazolium-based liquids, they observed that ANF exhibits an excitation-wavelength-dependent fluorescence spectrum.…”
Section: Gs(r T*)mentioning
confidence: 96%
“…This phenomenon, which is called the ''red-edge effect'' (REE), is characteristic of low-temperature glasses, polymers, and organized assemblies like micelles. As Samanta and coworkers (23) explain in their paper, this phenomenon is commonly due to heterogeneity in space (i.e., multiple solvation environments). It is surprising that little theoretical or computational work has considered the REE, although this phenomenon was first reported 30 years ago in several different systems (31)(32)(33).…”
Section: Gs(r T*)mentioning
confidence: 97%
See 1 more Smart Citation
“…51,52 Phosphate buffer solutions (PBS, 0.1 mol/L) were used as the supporting electrolyte. pH values of all solutions were adjusted by 0.1 mol/L phosphoric acid solution and 0.1 mol/L sodium hydroxide solution.…”
Section: Reagentsmentioning
confidence: 99%
“…Although many important results have been achieved in the field of bioapplications, basic studies still need to be carried out further, such as effects of the surrounding on the PL of water-soluble quantum dot NCs. In recent years, the previous work presented the effects of pH [6], ligands [7], and excitation wavelength [8] on the optical properties of water-soluble NCs for bioprobes [ 9]. Therefore, a phase transfer from oil to water is imperative to ensure the water solubility of the CIS NCs before further biological applications.…”
Section: Introductionmentioning
confidence: 99%